(untitled) (Universal International Scientific Journal, 2026)
This article discusses the features and capabilities of digital knowledge and modern technologies, which are of great importance in improving the quality of education of students studying in the modern era and have contributed to the many achievements of students in the education system, as well as contributing significantly to the further development of their knowledge, skills and qualifications. It also provides information on the use of information and communication technologies, interactive methods and innovative forms of education.